Techniques for Transforming Urban Development in the Historical Environment of Major City - Khachatryan, Tagush; Aghadjanyan, Lianna; Babajanyan, Grigor (Scientific Papers of National University of Architecture and Construction of Armenia, 2023)
The experience of transforming urban development within the historical center in different countries- mostly of Western Europe, as well as some examples of the synthesis of old and new architecture have been considered, in the light of its adaptation to new urban as well as socio-economic conditions. The main methods of reconstruction of individual buildings and ensembles have been identified - superstructure methods, extensions, inserts, hidden reconstruction, the existing state of development of Yerevan from the point of view of its renewal in accordance with the new needs of emerging society has been analyzed